Maximising clinical benefit with adequate patient management beyond the second line in mCRC. Issue 2 (13th May 2019) - Argiles, Guillem; Arnold, Dirk; Prager, Gerald; Sobrero, Alberto F; Van Cutsem, Eric
Abstract : New therapeutic options for refractory metastatic colorectal cancer (mCRC) include trifluridine/tipiracil (TAS-102) and regorafenib. However, the optimal chemotherapeutic regimen for use of each agent beyond the second line for patients with mCRC remains unclear and various factors may influence treatment decision. Available efficacy data suggest treatment with either trifluridine/tipiracil or regorafenib may be appropriate as both can extend patient survival. Thus, the safety profiles of each agent, along with patient performance status, are likely to determine treatment choice. The safety profiles of trifluridine/tipiracil and regorafenib are markedly different: higher levels of non-haematological adverse events such as fatigue, diarrhoea, hypertension and hand-foot skin reaction are reported with regorafenib, while haematological events such as neutropaenia are more common with trifluridine/tipiracil. In general, neutropaenia is a manageable treatment-related toxicity, while hand-foot skin reaction can be troublesome for patients, affecting their ability to carry out everyday activities and get on with their lives, while also affecting treatment adherence. Thus, the occurrence of any potential adverse effects and patient adherence should be closely monitored at each clinic visit. As quality of life is an important issue for patients with mCRC, it is important to balance extended survival and the likely quality of this extended life. Likewise, discussing possible side effects along with treatment expectations with patients can greatly facilitate adherence to therapy, and ultimately improve patients' quality of life and eventual clinical outcomes.